2011
DOI: 10.1097/sla.0b013e3182383118
|View full text |Cite
|
Sign up to set email alerts
|

Cytology Adds Value to Imaging Studies for Risk Assessment of Malignancy in Pancreatic Mucinous Cysts

Abstract: Objective Evaluate the value of cytology relative to imaging features in risk assessment for malignancy as defined in the Sendai Guidelines. Background The Sendai Guidelines list symptoms, cyst size > 30mm, dilated main pancreatic duct (MPD) > 6mm, mural nodule (MN) and “positive” cytology as high risk stigmata for malignancy warranting surgical triage. Methods We reviewed clinical, radiological and cytological data of 112 patients with histologically confirmed mucinous cysts of the pancreas evaluated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 51 publications
3
85
0
2
Order By: Relevance
“…Unfortunately, pre-operative evaluation of cytology in lesional fluid was not available in the majority of our cohort. While highly specific in the hands of an experienced GI cytopathologist, 43 studies have brought into question its utility when acellular material is aspirated and expert interpretation is not available. 44 In our study, cyst fluid samples from IPMN were assayed with high reliability for mAb Das-1 using standard techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, pre-operative evaluation of cytology in lesional fluid was not available in the majority of our cohort. While highly specific in the hands of an experienced GI cytopathologist, 43 studies have brought into question its utility when acellular material is aspirated and expert interpretation is not available. 44 In our study, cyst fluid samples from IPMN were assayed with high reliability for mAb Das-1 using standard techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the absence of high-grade atypia has been shown to provide a negative predictive value of > 90% for malignancy in the context of the absence of the high-risk imaging features of a dilated MPD and mural nodule, a so-called triple-negative test. 30 Our ability to preoperatively diagnose and manage patients with pancreatic mucinous cysts continues to evolve as we gain experience in all disciplines. The 2012 guidelines offer an improved algorithm for patient management that attempts to balance the risk of malignancy with the risk of surgery (Fig.…”
Section: Commentary 362mentioning
confidence: 99%
“…21 A cytological diagnosis of ''positive'' or ''malignant'' is generally 100% specific but very insensitive for detecting highgrade dysplasia. 30,31 Aspirating the contents of the cyst is really a screening test for the detection of dysplastic cells, akin to a Papanicolaou test. There is no directed biopsy of the cyst lining; the cells that are collected are those floating in the cyst cavity and adjoining ducts and abraded from the cyst wall with the aspiration needle.…”
Section: Commentary 362mentioning
confidence: 99%
“…The prevalence of incidental pancreatic cystic lesions found on Multidetector Computed Tomography (MDCT) has been reported to be as high as 2.6% [1]. Retrospective reviews of Magnetic Resonance Imaging (MRI) have shown an even higher prevalence of pancreatic cysts, from 13.5% to 19.6% [2,3]. Mucinous cystic neoplasm (MCN) and Intraductal Papillary Mucinous Neoplasm (IPMN) comprise up to half of all resected pancreatic cysts that are incidentally discovered [4,5].…”
mentioning
confidence: 99%
“…Cyst fluid Carcinoembryonic Antigen (CEA) level ≥192-200 ng/mL is close to 80% accurate for the diagnosis of a mucinous cyst, but the CEA level has no use in distinguishing benign from malignant cysts [7,18]. The addition of cytology in one study detected 30% more malignant lesions in small (<3 cm) BD-IPMN [19]. Molecular analyses of cyst fluid, notably KRAS and GNAS mutations, also offer promise in the diagnosis of malignancy [20,21].…”
mentioning
confidence: 99%